Determination of Total Phenol Content and GC-MS Analysis of Javanese Long Pepper Fruits Dried Using Two Different Methods - Syafitri, Meyke Herina (Journal of Research and Technology, 2024)
Javanese long pepper (Piper retrofractum Vahl.) contain kavicin, palmatic acid, tetrahydropiperic acid, piperidine, essential oils, and sesamin and the pungent substance piperine. This study to determine the total phenol content and phytochemicals remaining in the material after the drying process which analyzed by GC-MS. The first drying method was aerated (method I), while the second was boiled for a few minutes and dried in direct sunlight (method II). Dry powder then macerated with ethanol 96 % in 24 jam then continued with twice remaceration. The total phenol concentrations obtained were 23.64 mg GAE/g extract and 15.61 mg GAE/g for method I and II, respectively. The GC-MS chromatogram showed that 20 peaks detected in Method I, while 24 peaks in Method II. Compounds from the ethanol extract of Java Chilli in Method I were Ethanol, Piperidine, 1-[5-(1,3-benzodioxol-5-yl)-1-oxo-2,4-pentadienyl]-, (Z, Z)-, (2E,4E,14E)-N-Isobutylicosa-2,4,14, (E)-5-(Benzo[d][1,3]dioxol-5-yl)-1-(piperidin- 1-yl)pent-2-en-1-one. While the compounds from Method II which had the highest peaks, namely Piperidine, 1-[5-(1,3-benzodioxol-5-yl)-1-oxo-2,4-pentadienyl]-, (Z ,Z)-, Ethanol,8-Heptadecene, (2E,4E,14E)-N-Isobutylicosa-2,4,14, (2E,4E,10E)-N-Isobutylhexadeca-2,4,10-trienamide. The highest compounds contained in the ethanol extract of Javanese long pepper both two methods is piperidine.